2020
DOI: 10.33772/jitro.v7i1.8907
|View full text |Cite
|
Sign up to set email alerts
|

Kajian In Vitro Kecernaan Fraksi Serat Hijauan Tropis pada Media Cairan Rumen Kambing

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengevaluasi kecernaan NDF, kecernaan ADF dan kecernaan hemiselulosa pada hijauan pakan tropis secara in vitro. Materi yang digunakan dalam penelitian ini adalah 8 jenis pakan hijauan tropis dan cairan rumen kambing PE berfistula yang diberi pakan dengan kandungan PK 12% dan TDN 62%. Rancangan percobaan yang digunakan adalah rancangan acak lengkap 8 perlakuan pakan dan 3 ulangan. Perlakuan terdiri dari P1 = turi (Sesbania grandiflora), P2 = nangka (Artocarpus heterophyllus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
1
6
0
1
Order By: Relevance
“…In this study, the NDFD and ADFD were in the range reported by Hambakodu et al [18], i.e., 23.73 to 70.34% and 13.84 to 58.91%, respectively. The NDFD has a negative correlation with the lignin content of the fibre source [19]. The high NDFD can be caused by low lignin content and also affects the HSD.…”
Section: Dairy Fibre Feeds In Vitro Digestibilitymentioning
confidence: 99%
“…In this study, the NDFD and ADFD were in the range reported by Hambakodu et al [18], i.e., 23.73 to 70.34% and 13.84 to 58.91%, respectively. The NDFD has a negative correlation with the lignin content of the fibre source [19]. The high NDFD can be caused by low lignin content and also affects the HSD.…”
Section: Dairy Fibre Feeds In Vitro Digestibilitymentioning
confidence: 99%
“…The digestibility of NDF is higher than the digestibility of ADF because the NDF fraction still contains nutrients that are easily utilized by rumen microbes such as hemicellulose and cell wall proteins, while ADF contains many fractions that are difficult to digest, namely lignin and silica (Jamarun et al, 2017b); (Pazla and Jamarun 2021a). Similarly, Hambakodu et al (2020) highlighted that lignin levels have a negative correlation with ADF digestibility. The lower the lignin content, the higher the digestibility of ADF.…”
Section: Research Stage 2 a In Vitro Digestibilitymentioning
confidence: 98%
“…Kecernaan pakan dalam rumen dipengaruhi oleh kandungan lignin pakan, lignin yang ada dalam pakan menghambat kerja mikroorganisme rumen dalam mencerna pakan. Kandungan lignin yang rendah dalam pakan maka miroba rumen dengan mudah mencerna pakan hijauan tropis (Hambakodu et al, 2020). Kandungan nutrien rumput alam serta kecernaan nutrien masingmasing rumput alam yang tumbuh di lahan perkebunan dan padang penggembalaan perlu dievaluasi karena datanya masih terbatas.…”
Section: Pendahuluanunclassified